Influence of the dual qualification on the scope of practice of maxillofacial and oral surgery speciality in South Africa - Shalonga, Tinyiko Charmaine (My University, 2020)
Background: Entry requirements to MFOS speciality are either dentistry only or medicine only or both medicine and dentistry. The curriculum followed also varies in length, depth and quality, leading to significant differences in professional standards worldwide. Controversy exists over whether both dentistry and medicine are necessary in order to practice the full scope of MFOS. Aim: The aim of the study was to determine whether the current scope of practice of maxillofacial speciality is enhanced by dual qualification. Methods: A cross-sectional study, with convenience sampling was conducted. A questionnaire was sent via email and by hand to 103 dental professionals inclusive of 17 maxillofacial and surgeons and 11 registrars, Johannesburg-based dentists and University of the Witwatersrand dental students and specialists. Stata software, version 15, was used to analyse data, analysis was performed using Cohen's kappa coefficient and Fisher exact test. Results: Majority of surgeons had a dental degree only, their scope of practice was broad, even though some procedures were performed the least and by a few surgeons. Cohen's kappa coefficient revealed that there was agreement between procedures performed by surgeons and registrars, and perceptions by the dental community. Conclusion: The results were not conclusive to determine whether the current scope of practice of maxillofacial speciality is enhanced by dual qualification due to a small sample size. However, the study suggests that a broad scope of practice is performed by the surgeons even though the numbers were low.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Dentistry to the Faculty of Health Sciences, School of Maxillofacial and Oral Health Sciences, University of Witwatersrand, Johannesburg, 2020